Ecological and geochemical assessment of the territory of South Kazakhstan (the case of Turkestan and Kyzylorda regions) (Eurasian Journal of Ecology, 2021)
To identify the specifics of the formation of the elemental composition under the influence of a natural and anthropogenic factor, we conducted a study of the chemical composition of the hair of adolescents aged 16-18 years living in the territories of the Turkestan and Kyzylorda regions. Hair was taken as the object of research, since it is a depositing medium, in the structure of which chemical elements accumulate in high concentrations. The elemental composition was determined in a certified laboratory using instrumental neutron activation analysis. As a result of the study, for the Turkestan region, the following indicator elements were identified relative to the average for the sample: calcium, chromium, cobalt, rubidium, strontium, silver, barium, lanthanum, neodymium, samarium, europium, hafnium, thorium. For Kyzylorda region – scandium, bromine, rubidium, strontium, cerium, gold. A comparative assessment of the accumulation of elements in biosubstrates (hair) with other previously conducted studies revealed the following specific elements for the territory of South Kazakhstan – cerium, europium, scandium. The presence of the above listed elements in the hair of the population of South Kazakhstan can be explained by both the technogenic load and the geological component of the region.Key words: elemental composition, bioaccumulation, instrumental neutron activation analysis, bio-indication, technogenic impact, urbanized territories.